THE EFFECT OF REWARDS, TRANSFORMATIONAL LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE LOYALTY WITH JOB SATISFACTION AS A MODERATING VARIABLE AT PT PLN (PERSERO) CUSTOMER SERVICE IMPLEMENTATION UNIT (UP3) PADANGSIDIMPUAN - Berta Gracela Manalu; Kiki Farida Ferne; Sri Rahayu (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of rewards, transformational leadership, and work environment on employee loyalty with job satisfaction as a moderating variable at PT PLN (Persero) Customer Service Implementation Unit (UP3) Padangsidimpuan. This study is motivated by the importance of maintaining employee loyalty so that the company can achieve its goals effectively and sustainably. The population of this study was all employees of PT PLN (Persero) UP3 Padangsidimpuan with a total of 86 respondents determined through saturated sampling techniques. The research method used was quantitative with a questionnaire instrument analyzed using Partial Least Square (PLS). The results showed that rewards had a positive and significant effect on employee loyalty. Transformational leadership was proven to have a positive and significant effect on employee loyalty, as well as a conducive work environment that can increase employee loyalty. In addition, job satisfaction acts as a moderating variable that strengthens the relationship between rewards, transformational leadership, and work environment on employee loyalty. Thus, it can be concluded that to increase employee loyalty, companies need to pay attention to providing fair rewards, implementing transformational leadership, creating a comfortable work environment, and maintaining employee job satisfaction.